Late renal failure due to prostatic outflow obstruction: a preventable disease. Issue 6667 (21st January 1989) - Sacks, S. H.; Aparicio, S. A.; Bevan, A.; Oliver, D. O.; Will, E. J.; Davison, A. M.
Abstract : Nineteen patients presenting with late renal failure due to prostatic outflow obstruction (mean age 68.7 years; mean serum creatinine concentration 1158 mumol/l) were identified from the admission records of two renal units. As late renal failure secondary to prostatic enlargement is preventable case records were analysed retrospectively in an attempt to identify aspects of management in which preventive efforts might be of value. Delays in referral were common, with a mean of 2.8 years between the onset of prostatic symptoms and time of referral, six patients being referred who had had symptoms for more than three years. Four of five patients who had had a prostatectomy were known to be in renal failure at the time of operation but were not referred until 2-13 years later, when prostatic symptoms had recurred and there was evidence of progressive nephropathy with dilatation of the upper urinary tract. Two patients died on admission and eight (47% of survivors) required long term dialysis, most patients (80%) requiring some dialysis support during the initial period. These findings suggest that progressive nephropathy caused by prostatic outflow obstruction might, in part, be averted by more adequate screening of renal function in men with untreated prostatism and closer follow up of patients with uraemia at the time of prostatectomy.